Variability Studies in Palayankodan Ecotypes (AAB Genomic Group) of Banana (Musa Spp.) - Rajamanickam, C; Rajmohan, K (Journal of Horticultural Sciences, 2010)
Six Palayankodan ecotypes of banana belonging to AAB genomic group were evaluated for genetic variability among quantitative traits. Genetic and phenotypic coefficient of variation, heritability and genetic advance were estimated for eighteen traits that included plant height, pseudostem girth, number of leaves per plant, leaf width, number of suckers per plant, days taken from planting to shooting, total crop duration; length, girth, weight and volume of finger; hand weight, bunch weight, number of fingers per bunch, number of fingers per hand, ripe-fruit weight, sugar/acid ratio and pulp weight. Remarkable variability was observed among the collections for these characters. Bunch weight, number of fingers per bunch and number of suckers per plant with very high value of PCV, GCV, heritability and genetic advance makes it prime traits for direct selection. Plant height, pseudostem girth, total crop duration, sugar:acid ratio, finger length and days taken from planting to shooting with high value of heritability and moderate value of genetic advance. PCV are other important traits which need to be considered for selection. The volume of finger with low values for GCV, PCV, heritability and genetic advance as per cent of mean implies that it is highly influenced by environment and should not be taken as a criterion for selection. Plant height, total crop duration, sugar:acid ratio, finger length, pseudostem girth, number of fingers per bunch and days taken from planting to shooting showed high genetic advance and heritability and important characters to be considered for selection of ecotypes.
Keywords: Banana; Palayankodan; Ecotypes; Heritability; Genetic Advance; PCV; GCV